2013
DOI: 10.1186/1475-2867-13-104
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of miR-224 promotes cancer cell proliferation and invasion and predicts relapse of colorectal cancer

Abstract: BackgroundMicroRNAs (miRNAs) are small, non-coding RNAs that can function as oncogenes or tumor suppressors in human cancer. Abnormally expressed miR-224 was found to play a fundamental role in several types of cancer. The aim of this study was to investigate the prognostic and biological values of miR-224 in colorectal cancer (CRC).MethodsQuantitative RT-PCR (qRT-PCR) was used to evaluate expression levels of miR-224. The postoperative survival rate was analyzed with Kaplan–Meier method. The roles of miR-224 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 31 publications
0
42
0
Order By: Relevance
“…Smad4 contains two miR-224-binding sites in the 3′untranslated region and acts as a tumor suppressor role [21]. It was also reported that miR-224 acts as an oncogenic role in the cellular processes by targeting Smad4 in CRC [22]. The ectopic expressions of miRNAs may act as oncogenes which are closely related to the cancer development, and different signatures of miRNA expression distinguish the cancer cells from the normal ones [23].…”
Section: Mir-224 In Tumorigenesismentioning
confidence: 96%
“…Smad4 contains two miR-224-binding sites in the 3′untranslated region and acts as a tumor suppressor role [21]. It was also reported that miR-224 acts as an oncogenic role in the cellular processes by targeting Smad4 in CRC [22]. The ectopic expressions of miRNAs may act as oncogenes which are closely related to the cancer development, and different signatures of miRNA expression distinguish the cancer cells from the normal ones [23].…”
Section: Mir-224 In Tumorigenesismentioning
confidence: 96%
“…In terms of CRC, abnormal expression of several miRs such as miR-27b, miR-133b, miR-124 have been reported (Ye et al, 2013;Zhang et al, 2013b;Xiang and Li, 2014). Additionally, Zhang et al (2013a) found that ectopic expression of miR-224 promoted CRC tumor cell proliferation, migration, and invasion in vitro. Zheng et al (2014) indicated that downregulation of miR-132 in CRC was associated with tumor size, distant metastasis, and TNM stage.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-135a, b target APC gene to induce cell cycle progression and stimulate cell proliferation [48]. Zhang et al [49] reported that oncogenic miR-224 was significantly upregulated in CRC tissues and its overexpression in SW 480 cells promoted their proliferation. A tumor suppressor miR-185 (downregulated) inhibits division of CRC cells by targeting genes, RHOA (Ras Homolog Family Member A) and CDC42, involved in cell cycle progression; however, this mechanism appears to be cell-type specific [50].…”
Section: Mirna In the Pathogenesis Of Crcmentioning
confidence: 99%
“…Some of the upregulated miRNAs in CRC and their target genes miR-135/b APC Wnt-signaling pathway [54,95] miR-27 APC Promotes growth and metastasis [85] miR-221 RECK Stimulates invasion and metastasis [99] miR-210 RBM3 Promotes Angiogenesis [83,84] miR-21 CDC25A Cell cycle regulation [45] miR-31 RASA1 Promotes cell proliferation [47] miR-182 and miR-503 FBXW7 Tumor growth and progression [59] miR-200c ZEB1 and ZEB2 Metastasis [71] miR-224 PHLPP1, PHLPP1 Proliferation [49] miR-301a TGFBR2 Proliferation, migration [61] Some of downregulated miRNAs in CRC and their target genes miR-34a FRA-1 Invasion, migration [60] miR-137 Cdc-42,LSD-1 Tumor growth [133] miR-141 SIP1 Inhibits cell invasion and migration [134] miR-149 FOXM1 Proliferation, migration [62] miR-185 RHOA Cell cycle progression [50] miR-195 CARMA3 Promotes apoptosis [52] miR-215 TYMS,DTL Cell migration and proliferation [135] miR-330 CDC42 Cell proliferation [51] miR-339 --5p MDM2 Invasion, migration [64] miR-375 YAP1 Apoptosis [30] miR-455 RAF1 Proliferation [29] proliferation by targeting CARMA3 (Caspase Recruitment Domain Family, Member) and an inverse correlation is noted between miR-195 expression and CARMA3 protein expression [52].…”
Section: Identified Mirnamentioning
confidence: 99%